Introduction to pathophysiology of diabetic retinopathy - Kupis, Magdalena; Samelska, Katarzyna; Zaleska-Żmijewska, Anna; Szaflik, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
In recent years a systematic growing incidence of diabetes mellitus is being observed. Diabetic retinopathy – a microvascular complication of diabetes mellitus – is one of the leading causes of blindness among professionally active people. Pathophysiology of diabetic retinopathy remains unclear. Decreased retinal perfusion is one of the first observed changes in diabetic retinopathy. Hypoxia and hyperglycemia contribute to diabetic retinopathy development in multiple biochemical mechanism such as: increased sorbitol pathway, increased nonenzymatic protein glycation, increased activation of diacylglycerol and protein kinase C pathway, increased expression of growth factors such as vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1), haemodynamic changes, accelerated oxidative stress, activation of the renin-angiotensin-aldosterone system, subclinical inflammation with leukostasis. There is strong evidence that retinal neurodegeneration contributes to pathophysiology of diabetic retinopathy. A thorough analysis of these underlying pathogenic mechanisms may be useful for new effective pharmacological therapy discoveries.